Hadith #2347 - Sunan Abi Dawud - Abdullah bin al-N'man عبد الله بن النعمان السحيمي; Malazm bin 'Amr - Lazaym ملازم بن عمرو اليمامي - لزيم; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Qays bin Talq bin 'Ali al-Hanfi قيس بن طلق بن علي الحنفي اليمامي; Talq bin 'Ali bin al-Mundhar (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: The summons (adhan) of Bilal should not restrain one of you from taking a meal shortly before dawn, for he utters adhan or calls (for prayer) so that the man at prayer may return, and the man asleep may get up. Dawn is not (the whiteness) which indicates thus (in perpendicular) – the narrator Musaddad said: Yahya joined his palms (indicating the spread of whiteness vertically – until it indicates thus – and Yahya spread out two ring-fingers of his (d
Grade: Sahih